The Impact of Team Diversity, Task Interdependence, Team Conflict and Team Cooperation on Job Performance: Using Real Estate Brokers as Examples - Lee, Chun-Chang; Lee, Yu-Hsuan; Chen, Hsiao-Han; Hsieh, Pei-Shan; Yeh, Yung-Yun; Lin, Mei-Chu (International Journal of Management and Sustainability, 2014)
This study investigated the impact of team diversity, task interdependence, team conflict, and team cooperation on job performance. The research subjects were real estate brokers in Kaohsiung City, Taiwan, and the results were measured by a linear structural model. A total of 568 questionnaires were distributed, of which367 were retrieved. After eliminating the invalid samples, 362 valid questionnaires remained, with a valid return rate of 98.64%. According to the empirical results of the study, the following conclusions can be drawn: team diversity positively and significantly influences task conflict and relationship conflict; task interdependence positively and significantly influences job performance and team cooperation; task interdependence negatively and significantly influences relationship conflict; relationship conflict negatively and significantly influences team cooperation; and team cooperation positively and significantly influences job performance. In addition, team diversity and task interdependence were found to be critical exogenous factors of job performance.